Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0196592
|View full text |Cite
|
Sign up to set email alerts
|

A method for extracting high-quality total RNA from plant rich in polysaccharides and polyphenols using Dendrobium huoshanense

Abstract: Acquiring high quality RNA is the basis of plant molecular biology research, plant genetics and other physiological investigations. At present, a large number of nucleotide isolation methods have been exploited or modified, such as commercial kits, CTAB, SDS methods and so on. Due to the nature of different plants, extraction methods vary. Moreover, efficiency of certain approach cannot be guaranteed due to composition of different plants and extracting high quality RNA from plants rich in polysaccharides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 24 publications
3
53
0
3
Order By: Relevance
“…The comparative evaluation of these results allowed to determine that CTABbased methods were more efficient for isolating RNA from P. guajava leaves, whereby the CTAB2 protocol was the most efficient, isolating RNA with high purity, integrity and yields. These findings are compatible with other studies which demonstrated that methods based on guanidine salts, TRIzol ® and commercial kits were not effective for extracting RNA from species rich in secondary metabolites [4,7,35]. The CTAB-based methodology has also been used successfully by Jaakola et al (2001) for the extraction of high-quality RNA from Vaccinium myrtillus [40], and by Zeng & Yang (2002) in Cinnamomum tenuipilum [29], both perennial tree species.…”
Section: Guanidine Thiocyanatesupporting
confidence: 87%
See 1 more Smart Citation
“…The comparative evaluation of these results allowed to determine that CTABbased methods were more efficient for isolating RNA from P. guajava leaves, whereby the CTAB2 protocol was the most efficient, isolating RNA with high purity, integrity and yields. These findings are compatible with other studies which demonstrated that methods based on guanidine salts, TRIzol ® and commercial kits were not effective for extracting RNA from species rich in secondary metabolites [4,7,35]. The CTAB-based methodology has also been used successfully by Jaakola et al (2001) for the extraction of high-quality RNA from Vaccinium myrtillus [40], and by Zeng & Yang (2002) in Cinnamomum tenuipilum [29], both perennial tree species.…”
Section: Guanidine Thiocyanatesupporting
confidence: 87%
“…Most of the popular RNA isolation protocols are based on guanidine salts, such as the reagent TRIzol ® (Invitrogen, USA) and commercial kits like RNeasy ® (QIAGEN, Germany) and PureLink™ RNA (Invitrogen, USA). Although this method has been used successfully for the isolation of RNA from tissues of a variety of plants [30][31][32][33][34], for other species, protocols based on the guanidine method have proven to be unable to isolate quality RNA with satisfactory yields; besides, they increase the chances of co-purifying contaminants, which interferes with downstream applications [7,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…La obtención de ARN de alta calidad es la base de muchas investigaciones de biología molecular de plantas; RT-PCR, la síntesis de ADNc y el posterior análisis genético, requieren ARN con alta pureza e integridad (Liu et al, 2018). En la Figura 1, se puede observar la representación de las bandas características de las subunidades 28S y 18S del ARN ribosomal, con lo cual se confirma la purificación del ARN.…”
Section: Resultados Y Discusiónunclassified
“…En este estudio, la calidad del ARN total se detectó mediante la reacción en cadena de la polimerasa. Las muestras de ARN se transcribieron de forma inversa en ADNc y el resultado se amplificó usando PCR (Liu et al, 2018). De esta manera, se demuestra que el ARN total extraído de P. juliflora mediante el protocolo 1 y 3 cumplen con los requisitos para futuras investigaciones moleculares.…”
Section: Resultados Y Discusiónunclassified
“…After twenty days of infestation, leaf samples (three biological replicates) from each healthy control and infected seedlings were collected in liquid nitrogen for high molecular weight RNA extractions. RNA extraction buffer was prepared (Tris-HCl; 0.25 M, NaCl; 0.05 M, 20 mM; EDTA; (pH = 7.5); 1% (w/v) sodium dodecyl sulphate (SDS), 4% PVP w/v) as mentioned in the Liu et al 88 . The quality of RNA was checked on formaldehyde agarose gel electrophoresis and quantified using Qubit 3.0 with dsRNA broad range kit (Thermo Fisher, USA).…”
Section: Methodsmentioning
confidence: 99%